Social Observatory as a new space for civil society and government relationships in Belém, Pará State, brazilian Amazon - Barros, Jones Nogueira; Sobrinho, Mario Vasconcellos; Vasconcellos, Ana Maria de Albuquerque; Cançado, Airton Cardoso (Interações, 2019)
The article analyses the Social Observatory (SO) as a new arena for civil society, market and government dialogues and incidence on public policy. Specifically, the article examines the extent to which SO is an arena for a constructive dialogue to implement and to manage public policy for urban mobility at municipal level. It deals with the case of SO of Belém municipality, Pará State. Belém is the largest municipality in the Brazilian Amazon region in terms of population and socioeconomic structure for development. The paper shows that OS may constitute a significant participative arena which brings civil society and local government to take collective decision based on dialogue and transparency of information. However, since it is a new organizational pattern, the OS still have many difficulties and challenges, whether of internal character, whether in its relation to other actors in the municipal public, private power and civil society.